Chemical and physical weathering in a hot‐arid, tectonically active alluvial system of Anza Borrego Desert, California. Issue 5 (14th February 2016) - Joo, Young Ji; Elwood Madden, Megan E.; Soreghan, Gerilyn S.
Abstract: Investigation of chemical and physical weathering of bedrock and alluvial sediment in the Anza Borrego Desert, California, sheds light on weathering processes in hot‐arid systems and clarifies interpretations of climate from alluvial sediment. All of the alluvial sediment in the study area emanates from Cretaceous tonalite of the Peninsular Range, enabling exploration of the effects of external variables – climate, transport distance and tectonics – on the physical and chemical properties of the sediment. Chemical weathering in this area is dominated by plagioclase alteration observed in both bedrock outcrops and sediment, evinced most clearly by changes in the Eu anomaly. Biotite chemical weathering, manifested by interlayer K + loss, is not evident in bedrock, but clearly observed in the sediment. Despite the weak intensity of chemical weathering (Chemical Index of Alteration = 56 to 62), fine‐grained (<63 μm) sediment displays a clear weathering trend in A–CN–K space and contains up to 25% clay minerals. Physical abrasion and grain‐size reduction in biotite during transport predominates in the sediment, whereas physical (insolation) weathering affecting bedrock is inferred from estimates of differential thermal expansion of mineral phases in response to extreme temperature changes in the study area. Chemical alteration and Brunauer–Emmett–Teller surface area both increase within the active Elsinore fault zone at the distal end of the depositional transect, reflecting tectonic‐induced fracturing and associated accelerated weathering. Extensive fracturing, together with a more humid Pleistocene climate, probably facilitated in situ bedrock weathering, preceding arid alluvial deposition in the Holocene. This study demonstrates that both climate and tectonic processes can affect chemical and physical weathering, resulting in alteration of plagioclase, leaching of K + from biotite in the sediment and formation of clay minerals, even in hot, arid systems.